94.1k views
3 votes
Simplify the expression: 4 + 5(2x - 3) - 6x *

16x + 19
-16x -11
4x -9
4x + 9

User Vlz
by
6.1k points

2 Answers

4 votes

Explanation:

4+5 (2x-3)-6x

9 (2x-3)-6x

18x-27-6x

12x-27

User Stacked
by
6.4k points
3 votes

Answer:


\sf \: 4x - 11

Explanation:

Given expression,

→ 4 + 5(2x - 3) - 6x

Let's simplify the expression,

→ 4 + 5(2x - 3) - 6x

→ 4 + 10x - 15 - 6x

→ (10x - 6x) + (4 - 15)

→ (4x) + (-11)

→ 4x - 11

Hence, the answer is 4x - 11.

User Phylyp
by
5.4k points